NE‐RDFE: A protocol and toolkit for computing relative dissociation free energies with GROMACS between dissimilar molecules using bidirectional nonequilibrium dual topology schemes. Issue 12 (27th January 2023) - Macchiagodena, Marina; Pagliai, Marco; Procacci, Piero
Abstract: We describe a step‐by‐step protocol and toolkit for the computation of the relative dissociation free energy (RDFE) with the GROMACS molecular dynamics package, based on a novel bidirectional nonequilibrium alchemical approach. The proposed methodology does not require any intervention on the code and allows computing with good accuracy the RDFE between small molecules with arbitrary differences in volume, charge, and chemical topology. The procedure is illustrated for the challenging SAMPL9 batch of host–guest pairs. The article is supplemented by a detailed online tutorial, available at https://procacci.github.io/vdssb_gromacs/NE-RDFE and by a public Zenodo repository available at https://zenodo.org/record/6982932 . Abstract : NE‐RDFE provides a gromacs‐protocol for calculating RDFEs between chemically distant compounds differing in volume, Tanimoto and net charge. The article is complemeted by a public database and toolkit (https://zenodo.org/record/6982932 ) for reproducing RDFE data on the SAMPL9 hots‐guest systems and by a detailed step‐by‐step tutorial on the github web server (https://procacci.github.io/vdssb_gromacs/NE-RDFE/ ).